Monte Carlo Simulations of the GE Signa PET/MR for Different Radioisotopes - Caribé, Paulo R. R. V.; Vandenberghe, Stefaan; Diogo, André; Pérez-Benito, David; Efthimiou, Nikos; Thyssen, Charlotte; D’Asseler, Yves; Koole, Michel (Frontiers in Physiology, 2020)
NEMA characterization of PET-systems is generally based on 18F because it is the most relevant radioisotope for the clinical use of PET. Other commercially available PET radioisotopes, such as 82Rb and 68Ga have more complex decay schemes with a variety of prompt gammas, which can directly fall into the energy window and induce false coincidence detections by the PET-scanner. Methods: Aim of this work was threefold: (A) Develop a GATE model of the GE Signa-PET/MR to perform realistic and relevant Monte Carlo simulations (B) Validate this model with published sensitivity and NECR data for 18F and 68Ga (C) Use the validated GATE-model to predict the system performance for other PET isotopes including 11C, 15O, 13N, 82Rb and 68Ga and to evaluate the effect of a 3T magnetic field on the positron range. Results: Simulated sensitivity and NECR tests performed with the GATE-model for different radioisotopes were in line with literature values. Simulated sensitivities for 18F and 68Ga were 21.2 and 19.0cps/kBq respectively for the center position and 21.1 and 19.0cps/kBq respectively for the 10 cm off-center. The simulated peak-NECR was 216.8kcps at 17.40kBq/ml for 18F and 207.1kcps at 20.10kBq/ml for 68Ga. For 11C, 13N and 15O, results confirmed a peak-NECR similar to 18F. For 82Rb and 68Ga, the peak-NECR was lower than for 18F while the corresponding activity concentrations were higher. For the higher energy positron emitters, the positron range was confirmed to be tissue-dependent with a reduction of the positron range by a factor of 3-4 in the plane perpendicular to the magnetic field and an increased positron range along the direction of the magnetic field. Conclusion: Monte-Carlo simulations were used to predict sensitivity and NECR performance of GE Signa-PET/MR for 18F, 15O, 13N, 11C, 82Rb and 68Ga radioisotopes and were in line with literature data. Simulations confirmed that sensitivity and NECR were influenced by the particular decay scheme of each isotope. As expected, the positron range decreased in the direction perpendicular to the 3T-magnetic field. However, this will be only partially improving the resolution properties of a clinical PET/MR-system due to the limiting spatial resolution of the PET-detector.